Vegetation of the Northern Technogenic Landscape of South Yakutia - MIRONOVA, Svetlana I.; POISEEVA, Sargylana I.; KUDINOVA, Ziya A.; NIKIFOROV, Aleksey A. (Journal of Environmental Management and Tourism; Vol 8 No 7 (2017): JEMT Volume VIII Issue 7(23) Winter 2017DO - 10.14505//jemt.v8.7(23).07, 2018)
The paper represents the results of long-term studies of the vegetation of natural and technogenic landscapes of South Yakutia. The author has assigned two classes, two orders, five unions and 12 associations, characterizing the current state of vegetation of the studied region, with the Brown-Blanke ecological-floral classification. On the disturbed lands with open coal mining, the mountain vegetation in the fields is completely destroyed, instead of it only the succession processes are read, there are no stable communities. The author suggests carrying out measures for biological reclamation, which can restore the surrounding ecosystem.